Does Ethnicity Pay? Evidence from Overseas Chinese FDI in China - Huang, Yasheng; Jin, Li; Qian, Yi (The Review of Economics and Statistics, 2013)
Most of the economic analyses of the overseas Chinese network focus on trade and investment flows at the country level. In this paper, we analyze the effects of the ethnic Chinese network at the firm level. Contrary to the conventional wisdom, we find that ethnic Chinese FDI firms in China in fact underperform nonethnic Chinese FDI firms. We also find that the performance of ethnic Chinese firms deteriorates over time. We present evidence consistent with the hypothesis that ethnic Chinese firms underinvest in those firm attributes that may contribute to long-term performance, such as human capital and technology. Our findings raise both empirical and normative implications of ethnic ties.